The Determination of Cation Exchange Capacity of Napa Soil in 50 Kota Regency using Atomic Absorption Spectrophotometer - Mawardi Mawardi; Fadhlurrahman Mawardi; Illyas Md Isa; Sunyono Sunyono; Hary Sanjaya; Ilham Ardatul Putra; Vira Nilmania; Irfan Ananda Ismail (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
This research discuss about the cation exchange capacity of napa soil by using an atomic absorption spectrophotometer. The results is a value of the cation exchange capacity (CEC) and to review the differences of napa soil value and its influence on early treatment in the form of purification and treatment by using barium chloride method. According to the research that has been done, obtained  the optimum concentration of BaCl2 is 0.15 M and 0.15 M for MgSO4. Determination of CEC in optimum condition showed that napa soil that has been purified have higher CEC value, CEC value of napa soil in Situjuah Limo Nagari District is 1.7 meq/g and CEC value of napa soil in Sarilamak District is 1.2 meq/g. A fresh napa soil relatively has low value than napa soil that has been purified, the CEC value of  napa soil in Situjuah Limo Nagari District and Sarilamak District are 0.93 meq/g and 1.03 meq/g. While napa soil which has been given treatment with peroxide showed that CEC value declined sharply, the CEC value of napa soil in Situjuah Limo Nagari District and Sarilamak District which has been given treatment with peroxide are 0.3 meq/g and 0.7 meq/g.